Financial Elements in Teaching and Learning of Mathematics: A Systematic Review - Shazreen Amalin Saini , Noor; Rosli, Roslinda (International Research in Education, 2021)
Financial literacy is one of the 21st-century skills that are important for young people. Thus, integrating financial components in Mathematics subject is a way to instill financial literacy among students. This study aimed to determine the factor influencing the integration of financial elements and identify effective methods to enhance studentsʹ financial literacy. The research articles are collected from 2011 until 2019 through online databases known as Education Resources Information Center (ERIC), Sage Journals, Web of Science (WOS), ScienceDirect, and SCOPUS. The research finding shows that the factors affecting studentsʹ financial literacy were teaching methods and strategies, parental socialization, and school curriculum. It is essential to understand the influence of numerous factors. Knowing the factors that lead to or detract from the acquisition of financial literacy among students will improve their economic well-being by making policy initiatives. Financial socialization such as learning in school and parentsʹ involvement has become a significant factor in studentsʹ financial literacy. The practical methods used to enhance studentsʹ financial literacy consist of inquiry-based mathematics, technological simulation, interactive module, simulation games, workshops, and school camps.